Design Thinking and Innovation: Synthesising Concepts of Knowledge Co-creation in Spaces of Professional Development. (2nd January 2016) - Davis, John; Docherty, Catherine Ann; Dowling, Kate
Abstract: This paper explores how design thinking connects to concepts of knowledge creation and innovation. A case study of a knowledge sharing network in the social services sector is used to illustrate how design thinking supports Ba, the spaces for knowledge creation. Further exploration of the four enabling conditions for Ba resulted in delineation of two distinct types: relational and structural. Relational enablers support three groups of enabling conditions: interaction, shared values and communication. It is proposed that design thinking aligns well with relational enabling conditions for Ba to create the ideal spaces for knowledge creation. The group of structural enablers can assist or obstruct change and relate to the culture and management approaches of an organization, which may or may not be assisted by design thinking. However, to ensure that design thinking is not undermined, and innovation is achieved, the presence of an appropriate structural enabler is critical for success.